2003
DOI: 10.1073/pnas.0436428100
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian basal metabolic rate is proportional to body mass2/3

Abstract: The relationship between mammalian basal metabolic rate (BMR, ml of O 2 per h) and body mass (M, g) has been the subject of regular investigation for over a century. Typically, the relationship is expressed as an allometric equation of the form BMR ‫؍‬ aM b . The scaling exponent (b) is a point of contention throughout this body of literature, within which arguments for and against geometric (b ‫؍‬ 2/3) and quarter-power (b ‫؍‬ 3/4) scaling are made and rebutted. Recently, interest in the topic has been revive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
582
7
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(622 citation statements)
references
References 27 publications
30
582
7
3
Order By: Relevance
“…The reduced major-axis gradients of the log-converted relationships between both DEE and RMR and body mass (0.686 and 0.665) were consistent with allometry as predicted by the surface law (0.67) and observed empirically in other data sets (Heusner 1991;Dodds et al 2001;White and Seymour 2003). The gradient relating MLSP to mass was the same as that derived previously using a smaller data set (Lindstedt and Calder 1976).…”
Section: Discussionsupporting
confidence: 87%
“…The reduced major-axis gradients of the log-converted relationships between both DEE and RMR and body mass (0.686 and 0.665) were consistent with allometry as predicted by the surface law (0.67) and observed empirically in other data sets (Heusner 1991;Dodds et al 2001;White and Seymour 2003). The gradient relating MLSP to mass was the same as that derived previously using a smaller data set (Lindstedt and Calder 1976).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, we use BMR as a covariate, to test whether observed correlations are in fact based on differences in metabolic rates. Data on mammalian basal metabolic rate (BMR) and the concomitant body mass have been compiled using White and Seymour (2003) and Lovegrove (2000;. Basal metabolic rate is defined as the rate of metabolism of adult, post-absorptive, non-reproductive individuals during the resting phase, in their thermoneutral zone.…”
Section: Methodsmentioning
confidence: 99%
“…Basal metabolic rate is defined as the rate of metabolism of adult, post-absorptive, non-reproductive individuals during the resting phase, in their thermoneutral zone. For primate BMR data, we checked the original sources, because we found that some of results compiled in White and Seymour (2003) and Lovegrove (2000) contain data of immature, active or anaesthesized animals. For a complete list of primate BMR data, see .…”
Section: Methodsmentioning
confidence: 99%
“…Basal metabolic rate (BMR) is defined as the metabolic rate of inactive, post-absorptive, adult, non-reproductive animals in a thermoneutral setting. However, in published compilations such as Lovegrove (2000) or White and Seymour (2003), data derived from juveniles have often been included without comment. Some compilations of mammalian BMR contain data of active or anaesthesized animals, or species that have been inadvertently duplicated.…”
Section: Statistical Analysesmentioning
confidence: 99%